Kinematic parameter analysis and pilot clinical trial of dual-mobility semi-Knee prosthesis. (September 2019) - Li, Zhi; Liu, Peng; Ge, Jun; Huang, Chen; Chen, Guojing; Lu, Yajie; Cai, Xianhua; Xu, Feng; Sun, Jiuwei; Li, Jing; Wang, Zhen
Abstract: Background: To address large tumor-related defects and lower limb-length discrepancies during limb-salvage surgery in children with malignant tumors in the distal femur, a new custom-made dual-mobility semi-knee prosthesis (DMK) was made. This study aimed to provide a theory and references for further clinical applications of this prosthesis. Methods: Based on computed tomography data from adult knee joint samples, we used Mimics/Geomagic/Pro-E software and computer numerical control milling technology to design and manufacture the DMK. An in vitro study was carried out to examine the related kinematic parameters in the normal knee, total knee arthroplasty and DMK groups of cadaveric specimens. Then, a pilot clinical trial was performed. Results: The in vitro study revealed that the kinematics of the novel custom-made DMK are more similar to those of the normal knee than the total knee prosthesis. The pilot clinical trial showed that patients recovered well, and postoperative serial X-ray films did not demonstrate any disfigurations, loosening, dislocations or breaks in the prosthesis after a follow-up period ranging from 11 months to 5 years. Conclusion: The DMK is a novel concept and method for the treatment of malignant tumors in the distal femur in children, and the device used for ligament reattachment provides a solution for knee ligament reconstruction.However, DMK might be replaced by a total knee prosthesis after epiphyseal closure, because of incompatibility of tibial plateau with the prosthesis. Highlights: A new custom-made dual-mobility semi-knee prosthesis (DMK) was designed and made. DMK can handle lower limb-length discrepancies of limb-salvage surgery. Kinematics of the DMK are more similar to those of the normal knee in vitro study. Pilot clinical trial show good results after a follow-up from 11 months to 5 years. Development of the next generation dual-mobility semi-knee prosthesis is ongoing.